From stage to page - Jovićević, Aleksandra (Amfiteater (Ljubljana), 2022)
The paper deals with different forms of the performance text, still a new phenomenon in contemporary theatre, which requires new instruments for its analysis. The structural transformation of the written text into the performance, including the role of the spectator in it, confirms the fact that the performance text does not simply mean a new kind of the written text – and even less a new type of theatre text, but rather an essentially changed hypertext. Instead, the performance text could also be called an open text of the performance, in the sense that it requires spectators to become its active co-writers. Can we, therefore, define the performance text as a scenic écriture, collective writing, hypertext, stretch text, or even écriture corporelle? Furthermore, how can it be translated from stage to page to be preserved for future studies? The performance text is impossible without its author(s). Therefore, the paper deals with the performances of The Wooster Group, Motus, René Pollesch, Joris Lacoste, Milo Rau and Oliver Frljić, who are all constantly producing performance texts with their actors, without separating the process of writing from directing.
Keywords: actor; archive; arhiv; contemporary theatre; crystal image; dramaturgija; dramaturgy; gledališka igra; gledališka režija; gledališki gledalec; hipertekst; hypertext; igralec; kristalna podoba; narractor; performance art; performance text; performans; performer; pripovedovalec; pripovedovanje zgodb; repertoar; repertoary; sodobno gledališče; storytelling; theatre directing; theatre play; theatre spectator; uprizoritveno besedilo